Kaurenoic Acid from Aralia continentalis Inhibits Biofilm Formation of Streptococcus mutans. (4th April 2013) - Jeong, Seung-Il; Kim, Beom-Su; Keum, Ki-Suk; Lee, Kwang-Hee; Kang, Sun-Young; Park, Bok-Im; Lee, Young-Rae; You, Yong-Ouk
Abstract : We isolated a single chemical compound from A. continentalis and identified it to be kaurenoic acid (KA) and investigated the influence of anticariogenic properties. Inhibitory effects of KA on cariogenic properties such as growth, acid production, biofilm formation, and the adherence of S. mutans were evaluated. Furthermore, real-time PCR analysis was performed to evaluate the influence of KA on the genetic expression of virulence factors. KA significantly inhibited the growth and acid production of S. mutans at 2–4 μ g/mL and 4 μ g/mL of KA, respectively. Furthermore, the adherence onto S-HAs was inhibited at 3-4 μ g/mL of KA and biofilm formation was significantly inhibited when treated with 3 μ g/mL KA and completely inhibited at 4 μ g/mL. Also, the inhibitory effect of KA on biofilm formation was confirmed by SEM. In confocal laser scanning microscopy, bacterial viability gradually decreased by KA in a dose dependent manner. Real-time PCR analysis showed that the expressions of gtfB, gtfC, gbpB, spaP, brpA, relA, and vicR were significantly decreased in S. mutans when it was treated with KA. These results suggest that KA from A. continentalis may be a useful agent for inhibiting the cariogenic properties of S. mutans .